PENGARUH FINANCIAL LEVERAGE PADA INCOME SMOOTHING DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Chahyo Nugroho, 11.05.52.0151; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2016)
This research aimed to analyze the influence of leverage to income smoothingt and the ability to analyze the influence corporate governance consisting of institusional ownership, managerial ownership, institusional ownership, independent commisioner and audit commite in influencing income smoothing on the listed manufacturing companies spesifically consumer goods in Indonesia Stock Exchange during years 20011-2014. The sampling method in this study is purposive sampling metod found 104 companies in the sample. This study used secondary data obtained from the official website of the Indonesia Stock Exchange (IDX). Data analysis used logistic regression analysis and Moderated Regression Analysis (MRA). Index Eckel (1981) was used to determine the income smoothing. The hypotheseses were tested using binary logistic regression. The results show that the financial leverage had not effect on income smoothing. Good corporate governance proxied with managerial ownership and institutional ownership able to moderate the effect of financial leverage on good corporate income smoothing yet governance proxied by independent directors and audit committee is not able to moderate the effect of financial leverage on income smoothing.Keywords: Financial Leverage, Income Smoothing, Good Corporate Governance, Managerial Ownership, Institusional Ownership, Independent Commisioner And Audit Commite